“A look at Dangme Community Parlimentary voting pattern: A comparative review of elections Held in the various constituencies and what is likely to Happen in 2016 between NDC and NPP in the Dangme Constituency” - Nyarkotey Obu, Raphael (IJRDO - Journal of Social Science and Humanities Research, 2016)
“If water stays too long in a bottle it stinks”-Shai-Osudoku CPP Parlimentary candidate said. Others have said, they have eaten Banku for too long and therefore they have to try Pizza also. I decided to conduct this research as a postdoctoral work after my PhD in alternative medicine for Dangme media limited publishers of the monthly Dangme newspaper. There are various meanings and calls for change of Parlimenatry candidates in the Dangme land come December 2016. Are these calls something to be manifested? Can the Dangme people reject the NDC come December 2016? The Dangme land is for the National Democratic Party (NDC) but is the NDC for the good people of the Dangme land who have supported them faithfully not to talk of loyalty to the party for so many years. The people have started murmuring in the various constituencies as I toured the various constituecies in the course of my Dangme project aiming to redeem the Dangme land and bring it into national focus for discussion.  So special attention and developmental issues should be addressed. Most constituencies I toured some communities lack portable water, basic health eeds, unempolyment rates are very high, chieftiancy crisis with political undertones spiced the entire Dangme land et al . Most of the constituents believe they want to try a new thing , hence I have decided to conduct this research to assess the likelyhood of what could happen come December 2016. IJRDO-Journal of Social Science and Humanities Research ISSN : 2456-2971